Telecommunications-Related Services: Market Access, Deeper Integration and the WTO - Carlos A P Braga; Carsten Fink; Bernhard Hoekman (Hamburg Institute of International Economics (HWWA), 2002)
Liberalization and regulatory reform of telecom markets has emerged as a high profile policy issue. This paper analyzes how the multilateral system under the World Trade Organization can help developing countries in promoting their own information infrastructures. We focus on a specific ?regime? issue that has attracted increasing attention in recent years: the extent to which the WTO should pursue a ?deeper integration? agenda, using telecommunications and activities that rely heavily on telecommunications as a specific case. – – Die Liberalisierung und Reform der Telekommunikationsmärkte ist zu einem wichtigen politischen Thema geworden. Dieser Beitrag analysiert, wie das multilaterale System - unter der Welthandelsorganisation - Entwicklungsländern bei der Förderung ihrer eigenen Informations-Infrastruktur helfen kann. Wir konzentrieren uns auf eine spezifische ?Regime?-Frage, die in den letzten Jahren zunehmend Aufmerksamkeit erregt hat: In welchem Maße die WTO ein Programm der ?tieferen Integration? verfolgen sollte, das Telekommunikation als spezifischen Fall betrachtet.
Keywords: O19; F02; F13; L96; 330; International Economic Order; Trade Negotiations; Telecommunications Services; E-Commerce; Telekommunikationspolitik; Internationaler Dienstleistungsverkehr; WTO-Regeln; E-Business; Deregulierung; Welt; Entwicklungsländer